2008
DOI: 10.1007/s10558-008-9060-1
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Transient Multifield Analysis of a Piezoelectric Micropump for Drug Delivery System for Treatment of Hemodynamic Dysfunctions

Abstract: In this paper, we present design of a transdermal drug delivery system for treatment of cardiovascular or hemodynamic disorders such as hypertension. The system comprises of integrated control electronics and microelectromechanical system devices such as micropump, micro blood pressure sensor and microneedle array. The objective is to overcome the limitations of oral therapy such as variable absorption profile and the need for frequent dosing, by fabricating a safe, reliable and cost effective transdermal drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…In our previous study we presented the design of a controlled drug delivery system for the treatment of cardiovascular or hemodynamic disorders such as hypertension (Nisar et al 2008). In this work we present design and fabrication of hollow out-of-plane silicon microneedles to integrate with previously fabricated piezoelectrically actuated valveless micropump (Nisar et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study we presented the design of a controlled drug delivery system for the treatment of cardiovascular or hemodynamic disorders such as hypertension (Nisar et al 2008). In this work we present design and fabrication of hollow out-of-plane silicon microneedles to integrate with previously fabricated piezoelectrically actuated valveless micropump (Nisar et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this work we present design and fabrication of hollow out-of-plane silicon microneedles to integrate with previously fabricated piezoelectrically actuated valveless micropump (Nisar et al 2008). All the numerical studies reported in literature on the design and analysis of silicon microneedles cover either structural or fluid analysis only.…”
Section: Introductionmentioning
confidence: 99%
“…The mass flow rate is provided per unit depth of the device (a two-dimensional model is considered). While the previous studies [2,4,6,7,10,18,19] report on the maximum value of instantaneous flow rates, instantaneous velocities are integrated along the outlet at each time step during one perturbation cycle in the present study. The instantaneous flow rates can be adjusted by varying parameters such as applied electric potential, actuation frequency, and geometric variables.…”
Section: Acoustically Driven Flows In a Micropump: Quasi-periodic Statementioning
confidence: 99%
“…It can be calculated by multiplying the Flexinol length and unit resistance, which is given as a characteristic of the Flexinol. resistance = unit resistance (ohm/cm) × flexinol length (cm) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) Flexinol efficiency in Eqn (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) refers to the kinetic energy it can generate divided by the electrical energy required to generate it. From this equation, the current that is required to contract the Flexinol during the given contraction time can be calculated.…”
Section: Design Parmeters For Flexinol Designmentioning
confidence: 99%
“…From this equation, the current that is required to contract the Flexinol during the given contraction time can be calculated. V required V = current × resistance (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) No. of Flexinol/finger refers to number of Flexinols that should be connected to each finger.…”
Section: Design Parmeters For Flexinol Designmentioning
confidence: 99%